Pathophysiology study guide - Copstead, Lee Ellen (Elsevier, Saunders, 2014)
Explores the etiology, pathogenesis, clinical manifestation, and treatment of disease. This title includes units that cover a specific body system and begin with an illustrated review of anatomy and normal physiology to prepare you for disease processes and abnormalities discussions. It covers the developments in pathophysiology